EXPLORING THE ROLE OF SELF-EFFICACY IN THE IMPLEMENTATION OF SELF-ASSESSMENT FOR ENGLISH WRITING - A.A.G.Y., Paramartha, (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2016)
Many researchers have pointed out that the use of self-assessment gives positive effect on students’ writing performance. However, some other factors, such as students’ self-efficacy which may also play a role for students’ success in writing is still rarely studied. Both self-assessment and self-efficacy share linear effect on students’ writing performance. Thus, observing students with high and low self-efficacy while they are using self-assessment in writing is considerably noteworthy to study. This research is interested in investigating the role of high and low self-efficacy in the implementation of self-assessment for English writing. The design of the research was Pre-experimental Design of One-Shot Case Study with the sample of 42 students. The data were collected by using self-efficacy questionnaire and writing competency scoring rubric. The data were analyzed by using t-test. The result shows that there is a significant difference between students with high and low self-efficacy on the implementation of self-assessment for English writing.